Eksistensi Trowulan dalam Peradaban Nusantara : Majapahit pada Masa Pemerintahan Rajasanagara - Al Hafiz Rasya Ramadhan; L.R. Retno Susanti; Hudaidah Hudaidah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Majapahit was a maritime empire which in its heyday controlled most of the archipelago. Majapahit's global political and commercial influence extended to all corners of the archipelago, so that Majapahit was known as a large empire with amagnificent fleet. The glory of Majapahit was obtained during the reign of Rajasanagara who succeeded in introducing Majapahit outside Java and recognized the sovereignty of his kingdom by regions outside Java or the Archipelago. This research is a descriptive qualitative research using historical methods with heuristic stages, source criticism, interpretation and historiography. This research produces a description of the Majapahit kingdom which reached its peak of glory and power when it was led by Rajasanagara with the center of its kingdom being in Trowulan.This is evidenced by relic sites and findings from the Majapahit era found at theTrowulan site. The progress of the Majapahit civilization can be seen from the buildings erected, the art of statues and the famous law and literature books.